Analisis Kandungan Asam Sianida (HCN) pada Rebung Bambu Kapal (Gigantochloa schortechinii) sebagai Bahan Makanan - Roleka Julia Marcellina; Bhakti Karyadi; Rendy Wikrama Wardana; Euis Nursa’adah; Afrizal Mayub (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2025)
This study aims to determine the effect of different lengths of soaking on cyanide acid (HCN) content in ship bamboo shoots (Gigantochloa schortechinii) which are the main ingredient in making Lemea. Lemea is a specialty food of the Rejang tribe in Bengkulu Province where the main ingredient of Lemea is fermented chopped bamboo shoots (young bamboo). This study used a completely randomized design (CRD) with five repetitions and four treatment levels, namely. A = no treatment/control, B = 4 days soaking, C = 5 days soaking, D = 6 days soaking and E = 7 days soaking. The results of the analysis showed that different lengths of soaking time had an effect on reducing cyanide acid (HCN) content. The highest to lowest average cyanide acid (HCN) content was obtained from treatments A (70.066 ppm), B (53.759 ppm), C (42.374 ppm), D (29.739) and E (16.458 ppm). The best cyanide acid (HCN) content was obtained in the immersion treatment for 7 days with an average HCN content of 16.458 ppm, this result is highly recommended because the HCN content is safe for consumption according to FAO (Food and Agriculture Organization).